Ikhtiar Mahasiswa KKN STIBA Makassar dalam Pembentukan Akhlak Qur'ani Masyarakat Desa Balassuka Kabupaten Gowa - Rachmat Bin Badani Tempo; Khaerul Aqbar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
Balassuka Village is a village located in the Tombolo Pao District in the eastern part of Gowa Regency with a distance of around 88 km from the city of Sungguminasa, and a distance of 15 km from the capital district with a total area of approximately 29 km2. The village with its various problems in the economic, social, educational, health, religious and cultural fields is in need for problem solving and for village development program. The objective of STIBA Makassar Community Service Program (KKN) in Balassuka Village was to implement higher education tri dharma on the pillar of community service. The method of community service (PkM) implementation was started by conducting a field survey using an independently-made instrument, and afterwards an SOAR analysis was performed for the purposes of preparing the KKN programs. KKN programs were generally divided into three those were the Koran education program, training, and community development. The Koran Education Programs were TK/ TPA, Dirosa (Koran Learning Program for Adult), Tahsinul Qira’ah, and discourse of the book Qawaid Qur'aniyah. Training programs included funeral arrangement training. Community development Program included Friday sermon, Taklim for youth and common people, brief Islamic speech every Magrib; Friday for worship; majlis taklim; and coaching for young mosque caretakers. The results of KKN activities show that the community and local government are very enthusiastic and grateful for the benefits they obtained from the implementation of KKN students’ work programs in Balassuka Village. In terms of knowledge, the community has experienced the development of Islamic insight. In terms of skills a change is seen in the recitation of makhraj and tajweed in reading the Koran. In terms of affection, the community begins to realize and be enthusiastic in performing worship that is based on proper and correct religious knowledge.